Regulatory roles of three-dimensional structures of chromatin domains - Kelly Yichen Li; Qin Cao; Savio Ho-Chit Chow; Chiara Nicoletti; Pier Lorenzo Puri; Huating Wang; Danny Leung; Kevin Y. Yip (Genome Biology)
Abstract Background Transcriptional enhancers usually, but not always, regulate genes within the same topologically associating domain (TAD). We hypothesize that this incomplete insulation is partially due to three-dimensional structures of corresponding chromatin domains in individual cells: whereas enhancers and genes buried inside the core of a domain interact mostly with other regions in the same domain, those on the surface can more easily interact with the outside. Results Here we show that a simple measure, the intra-TAD ratio, can quantify the coreness of a region with respect to the single-cell domains to which it belongs. We show that domain surfaces are permissive for high gene expression. Cell type-specific active cis-regulatory elements, active histone marks, and transcription factor binding sites are enriched on domain surfaces, most strongly in chromatin subcompartments typically considered inactive. Conclusions These findings suggest a model of gene regulation that involves positioning active cis-regulatory elements on domain surfaces. We also find that disease-associated non-coding variants are enriched on domain surfaces.